Energy-windowed, pixellated X-ray diffraction using the Pixirad CdTe detector. (4th January 2017) - O'Flynn, D.; Bellazzini, R.; Minuti, M.; Brez, A.; Pinchera, M.; Spandre, G.; Moss, R.; Speller, R.D.
Abstract: X-ray diffraction (XRD) is a powerful tool for material identification. In order to interpret XRD data, knowledge is required of the scattering angles and energies of X-rays which interact with the sample. By using a pixellated, energy-resolving detector, this knowledge can be gained when using a spectrum of unfiltered X-rays, and without the need to collimate the scattered radiation. Here we present results of XRD measurements taken with the Pixirad detector and a laboratory-based X-ray source. The cadmium telluride sensor allows energy windows to be selected, and the 62 μ m pixel pitch enables accurate spatial information to be preserved for XRD measurements, in addition to the ability to take high resolution radiographic images. Diffraction data are presented for a variety of samples to demonstrate the capability of the technique for materials discrimination in laboratory, security and pharmaceutical environments. Distinct diffraction patterns were obtained, from which details on the molecular structures of the items under study were determined.